IMPLEMENTATION OF CHARACTER EDUCATION IN LEARNING AQIDAH AKHLAK - Nenda Nenda; Rini Setyowati; Saiful Muktiali; Siti Juariah (Jurnal Scientia, 2023)
This research is based on a case study of researchers' anxiety about the character of a nation that is experiencing moral decadence, including increased promiscuity, drug abuse, and so on. In this case the Integrated Islamic Elementary School in the Aqidah Akhlak subject has a big role in raising awareness of Islamic religious values to students. This study uses a qualitative method. The research location is SDIT Armaniyah Serang Baru. Data collection is done by observation, interviews, and documentation. Data analysis was performed by cross-case analysis. The results of the study show that Aqidah Akhlak teacher learning planning as an effort to build character is by designing a learning plan involving the media, the application of Aqidah Akhlak teacher learning in an effort to shape the character of students is carried out referring to the rules and regulations that have been planned and determined in every activity or learning process in Integrated Islamic Elementary School educational institutions as Elementary Education Institutions, evaluation of Aqidah Akhlak teacher learning in the form of assignment tests from teachers, daily tests, UTS scores and students' UAS tests. The delivery of Aqidah moral learning in the formation of the character of students is applied by subject teachers in schools where research with satisfactory results.